(3TQM GdQhVI aj CUhd Gdabg Ydi ePgH GdEeGe CMeO Hf MfHd ddTjN ehab GdOjf GdMfHdis - (3CHh GdQHjY fLe GdOjf SdjeGf Hf YHO Gdbhi Hf YHO GdcQje GdWhai GdUQUQis; (3YHO Gddg Hf eMeO Hf bOGeI GdLeGYjdj GdebOSj Ke GdOeTbj GdMfHdj, CHh eMeO, ehab GdOjf,(B620 (3g`s ((3CMeO Hf Ydi GdTLQi GdTGaYi s)
(3ChdgG (B:s
(3hjMJed gGgfG Cf jbOe bhd GdeYOd dCf GdSdc GdPi GSJfO Gdjg GdLGQM bO JHjf HWdGfg s
(3BNQgG (B:s
(3hGdYHGQGJ ai JYQja GdbjGSi cKjQI hMGUdgG jQLY Edi Efg GYJHGQ GdaQY ai Mceg hGddg SHMGfg hJYGdi GYde BNQ GdLRA GdKGfi ef TQM GdhQVI s
(3GdfSNI HgG MhGTs
(3HgG CKGQ JbWjY hQO GdYfhGf GdCUdi ai c X (B1 / 930s
(3cJHJ HNW eged GdfbW s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3CUhd Gdabgs